2018
DOI: 10.12911/22998993/92891
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of Biochar-Compost and Phosphate Solubilizing Fungi from Oil Palm Empty Fruit Bunch to Improve Growth of Maize in an Ultisol of Central Kalimantan

Abstract: The efficiency of phosphorus uptake by plants in an Ultisol soil is very low because most of the soil phosphorus is precipitated by Al and Fe. Oil palm empty fruit bunches can be used as basic materials of biochar and compost, and as sources of isolates of phosphate solubilizing fungi. This study was aimed at elucidating the effect of application of phosphate-solubilizing fungi with biochar and the compost produced from oil palm empty fruit bunches on the growth and yield of maize an Ultisol of Central Kaliman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 35 publications
0
31
0
5
Order By: Relevance
“…PSMs are diversified in nature, as listed in Table 3. Bacteria belonging to the genera Pseudomonas, Enterobacter, and Bacillus (Biswas et al 2018;Buch et al 2008), Serratia and Pantoea (Sulbaran et al 2009), Rhizobium, Arthrobacter, and Burkholderia, and Rahnella aquatilis HX2 (Liu et al 2019a;Zhang et al 2019), Leclercia adecarboxylata (Teng et al 2019a), and fungi like Penicillium brevicompactum and Aspergillus niger (Rojas et al 2018;Whitelaw 1999), and Acremonium, Hymenella, and Neosartorya (Ichriani et al 2018) are potent PSMs. These soil microbes perform a significant role in soil by their metabolic activities and are a remarkable part of integrated nutrient management in the soil, as they improve the plant's nutrient acquisition from the soil.…”
Section: Phosphate-solubilizing Microorganisms (Psms)mentioning
confidence: 99%
“…PSMs are diversified in nature, as listed in Table 3. Bacteria belonging to the genera Pseudomonas, Enterobacter, and Bacillus (Biswas et al 2018;Buch et al 2008), Serratia and Pantoea (Sulbaran et al 2009), Rhizobium, Arthrobacter, and Burkholderia, and Rahnella aquatilis HX2 (Liu et al 2019a;Zhang et al 2019), Leclercia adecarboxylata (Teng et al 2019a), and fungi like Penicillium brevicompactum and Aspergillus niger (Rojas et al 2018;Whitelaw 1999), and Acremonium, Hymenella, and Neosartorya (Ichriani et al 2018) are potent PSMs. These soil microbes perform a significant role in soil by their metabolic activities and are a remarkable part of integrated nutrient management in the soil, as they improve the plant's nutrient acquisition from the soil.…”
Section: Phosphate-solubilizing Microorganisms (Psms)mentioning
confidence: 99%
“…Various attempts have been made to increase the availability of P in Ultisols by the addition of inorganic fertilizers, as well as organic matters into the soil. The results of previous studies showed that the application coal fly ash (CFA), which was combined with phosphate-solubilizing fungi (PSF), and compost from oil palm empty fruit bunches (OPEFB) could increase the availability of P in an Ultisol of Kalimantan (Ichriani et al, 2017;Ichriani et al, 2018;Fahrunsyah et al, 2018;Wilujeng and Handayanto, 2019). However, the increase was not yet optimal.…”
Section: Introductionmentioning
confidence: 99%
“…The non-optimal role of PSF was suspected to be related to the lack of adaptation of PSF in the carrier media used. Ichriani et al (2017) succeeded in getting four PSF isolates from OPEFB, namely Acremonium ciliens, Aspergillus oryzae, Hymenella Fr., and Neosartorya fischeri. Each of the four PSF isolates could increase available P by 451%, 400%, 216% and 114%, respectively on the 5th day in liquid Pikovskaya media containing tricalcium phosphate (Ichriani et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effect of the treatment on dry seed weight was not significantly different from the A20K20, A40K10, A40K20, and A80K10 treatments. The application of materials generated from oil palm empty fruit bunch (biochar, compost, and phosphate solubilizing fungi) on Ultisol of Kalimantan significantly improved the growth and yield of maize, as well as its the phosphorus uptake and uptake efficiency (Ichriani et al, 2018). Ekpo et al (2014) revealed that oil palm empty fruit bunches amendments were able to ameliorate the effect of the crude oil pollution as well as enhance the germination and growth performance of the white mangrove (Laguncularia racemosa) species.…”
Section: Yield Components Of Maizementioning
confidence: 99%